PREVALENCE OF INTESTINAL HELMINTHIASIS IN CITY AND VILLAGES IN WESTERN IRAN - E.Ghadirian; F.Arfaa; Gh.Missaghian; H.Bahrani (Tehran University of Medical Sciences, 1973)
Inhabitants of 4 districts in the city of Kermanshah, the capital of province, living under various socio- economic conditions, were examined for infection with intestinal helminthiasis. Two of these districts were close to and the other two far from a small stream running through the city and serving as an unsanitary sewage system. A total of 889 persons in different sex and age groups from these 4 areas and 57 students of a nursing school in the city were examined. In addition, a total of 933 inhabitants of 10 villages, 5 in the vicinity of Kermanshah city and 5 in the Qasr-e-Shirin area in the western part of the province, were also examined. A surprising high prevalence of infection with Ascaris and Trichuris was found among the inhabitants of all 4 districts, the mean prevalence being 74% for Ascaris and 64% for Trichuris. The prevalence of Trichostrongylus spp. and H.Nana was less than 7% in all areas. The prevalence of Ascaris and Trichuris did not differ very much in the various sex and age groups except in the age group below 5, which had lower infection rates. The prevalence of these two infections was similarly high among the inhabitants of the villages. (A mean infection rate of 78% for Ascaris and 58% for Trichuris). The highest rate of Ghaleh Sabzi near Qasr- e-Shirin city, the species of Trichostrongylus expelled from treated patients were T. colubrifromis , T.vitrinus T. capricola . Species found in animals were T. vitrinus T. colubriform , T. axei and T. capricola. The factors responsible for the high rate of infection among the population of the city are discussed.